The Violation of Labour Rights in Plastic Sector: A Study on Plastic Factory Workers in Bogura Sadar Upazila: - Sumona Sharmin; Md Mehedi Hasan (GAYAKU PUBLISHER, 2023)
A large number of workers work in plastic sector. The Bangladesh Labour Act, 2006 provides legislation to ensure the rights of workers. But this act does not followed accordingly in plastic sector. For this reason, the rights of the plastic factory workers are violated in many ways. This paper mainly analyzes the nature, patterns and cause of labour rights violation of plastic factory workers. This is a descriptive study and data have been collected from the workers of plastic factories in Bogura sadar, Bogura. The findings of the study shows that, plastic factory workers faced the following rights violation such as low wage, long working hour, low overtime payment, gender discrimination, inhuman behavior, unhealthy and unhygienic condition of workplace, lack of safety and security etc. Finally the study suggests that, the proper enforcement of existing labour act can reduce the violation of labour rights in this sector. Â